Multiobjective Optimization in Health Care Management. A metaheuristic and simulation approach. - Azcárate, Cristina; Mallor, Fermín; Gafaro, Aurora (Algorithmic Operations Research)

(untitled) (Preeminent Academic Facets Inc., 2008)
This paper describes a methodology which combines elements of statistics, probability, mathematical programming, simulation, multiobjective optimization and metaheuristics, to analyze management problems in a health care context. We apply this approach to a staffing problem in a primary care center, taking into account both cost and service quality criteria. We illustrate our approach with a case study.